Peran Guru dalam Membentuk Karakter Religius Peserta Didik Kelas III Madrasah Ibtidaiyah Ma’had Al-Zaytun - Annisa Alfath; Moh. Mas’ud Arifin; Dadan Mardani (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2026)
The character crisis among students has become a serious concern, marked by the rise of deviant behaviors such as bullying, drug abuse, and criminal acts committed by minors. This phenomenon underscores the urgent need to strengthen religious character through the active role of teachers in the school environment. This study aims to describe the role of teachers in shaping the religious character of Grade III students at Madrasah Ibtidaiyah Ma'had Al-Zaytun, as well as to identify the supporting and inhibiting factors in the character formation process. A qualitative approach was employed, with data collected through in-depth observation, interviews, and documentation. Research subjects were determined using snowball sampling, while data validity was verified through source triangulation, technique triangulation, and time triangulation. The findings reveal that teachers play multiple strategic roles in shaping students' religious character, including acting as educators, instructors, mentors, motivators, evaluators, facilitators, and advisors, as well as serving as role models and fostering habitual religious practices. Supporting factors in religious character formation include the availability of school facilities and infrastructure, along with various religious activities within the school environment. Inhibiting factors consist of internal factors related to students' individual characteristics and external factors stemming from the home environment. These findings affirm that the teacher's role is multidimensional and requires synergy between the school and family environment to effectively cultivate strong religious character in students.